COVID-19 and the voluntary and community sector in the UK : responses, impacts and adaptation - Rees, James, 1978- (Policy Press, 2022)
Curating rigorous academic, policy and practice-based research, this book explores the response and adaptation of the UK voluntary sector to the COVID-19 pandemic and considers what can be learned to maximise its contribution in the event of future crises.